(untitled) (Bioagro, 2022)
The "gray mold" is one of the main diseases of the blueberry crop that causes economic losses, the causal agent is the fungus Botrytis cinerea. The application of fungicides is one of the main strategies for its management; however, the pathogen has developed resistance to groups of fungicides. In search of a new control alternative, the antagonistic activity of 40 strains of endophytic fungi (EF) on B. cinerea was evaluated at the National University of Cañete. Antibiosis tests were performed with the extraction of secondary metabolites from the strains of HE and mycoparasitism with the method pre-colonized plate by the pathogen, where the mycelial inhibition of the pathogen and HE colonization, respectively, were evaluated. The metabolites obtained from the genus Aspergillus (strain 111) completely inhibited the mycelial growth of pathogen, followed by the genera Nigrospora (58) and Aspergillus (117) with 89.82 % and 63.33 % respectively compared to Cladosporium (116) which had less effect towards the pathogen with 3.19 % mycelial inhibition. However, all the strains of the genus Trichoderma (1, 91, 93 and 94), Alternaria (5 and 78), Fusarium (106), Cladosporium (41) and Lasiodiplodia (49) completely colonized the pathogen and were considered as more aggressive mycoparasites followed of the 117 and 111 Aspergillus strains that colonized 83.33 % and 63.33 % to the pathogen respectively. These endophytic fungi with antagonistic activity towards B. cinerea could be used as an alternative for disease control in blueberry cultivation.